2012
DOI: 10.1007/s00422-011-0460-8
|View full text |Cite
|
Sign up to set email alerts
|

Using individual-muscle specific instead of across-muscle mean data halves muscle simulation error

Abstract: Hill-type parameter values measured in experiments on single muscles show large across-muscle variation. Using individual-muscle specific values instead of the more standard approach of across-muscle means might therefore improve muscle model performance. We show here that using mean values increased simulation normalized RMS error in all tested motor nerve stimulation paradigms in both isotonic and isometric conditions, doubling mean simulation error from 9 to 18 (different at p < 0.0001). These data suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…There is no simple, linear relationship between motor neuronal activity and muscle force (Hooper and Weaver 2000). Moreover, fitting data to models requires unique parameters for each individual (Blümel et al 2012). During biting, the I2 muscle does not activate immediately even if stimulated at high frequency (Hurwitz et al 1996;Yu et al 1999).…”
Section: Variability Biomechanics and Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…There is no simple, linear relationship between motor neuronal activity and muscle force (Hooper and Weaver 2000). Moreover, fitting data to models requires unique parameters for each individual (Blümel et al 2012). During biting, the I2 muscle does not activate immediately even if stimulated at high frequency (Hurwitz et al 1996;Yu et al 1999).…”
Section: Variability Biomechanics and Behaviormentioning
confidence: 99%
“…Averaging parameters from many animals may not solve this problem. A study of model oscillators demonstrated that averaged parameters did not generate oscillations (Beer et al 1999), a study of a conductance-based model neuron demonstrated that averaged parameters did not generate physiologically relevant behavior (Golowasch et al 2002), and using parameter sets measured from individual animals improved muscle models compared with using averaged values (Blümel et al 2012).…”
mentioning
confidence: 99%
“…6.4), as the measured velocity would depend on both CE properties and D line acceleration over the measurement interval. Alternatively, including D line mass improves model stability, and such models can give very good results (Blümel et al 2012b). Perhaps the most correct conclusion is that the model in the 'a' panels of Figs.…”
Section: Combining the Model Componentsmentioning
confidence: 94%
“…This approach, in which V CE changes in a non-history dependent fashion to always make F CE + F PE = F SE , is not always used (Blümel et al 2012b;Cheng et al 2000). In these models V CE is updated by calculating dV CE /dt each time step (Δt) and adding Δt · dV CE /dt to the prior V CE to obtain a new V CE .…”
Section: Combining the Model Componentsmentioning
confidence: 99%
See 1 more Smart Citation